Stem cell marker nestin is expressed in plasma cells of multiple myeloma patients - Svachova, H; Pour, Luděk; Sana, J; Kovarova, L; Raja, K R Muthu; Hajek, R (Leukemia research, 2011)
Nestin is considered to be a characteristic marker of multipotent proliferative precursors found in some embryonic and fetal tissues. Its expression might be a suitable diagnostic and prognostic indicator of malignancy and a potential marker of cancer stem cells in solid tumors. Unexpectedly, nestin protein was detected in mature CD138(+)CD38(+) plasma cells of multiple myeloma patients and statistical analysis confirmed significant differences between myeloma patients and control group without hematological malignancy. Our results represent the first evidence of nestin expression in multiple myeloma. Further studies are required to elucidate the role of this protein in multiple myeloma.
Keywords: imunofenotypizace; dospělí; nádorové biomarkery; Blotting, Western; Prognosis; senioři nad 80 let; studie případů a kontrol; Biomarkers, Tumor; Pilot Projects; Humans; lidé středního věku; proteiny intermediálních filament; Aged, 80 and over; Middle Aged; Multiple Myeloma; prognóza; mužské pohlaví; Flow Cytometry; Adult; plazmatické buňky; Plasma Cells; průtoková cytometrie; Nerve Tissue Proteins; Immunophenotyping; ženské pohlaví; nádorové kmenové buňky; western blotting; lidé; Case-Control Studies; Neoplastic Stem Cells; pilotní projekty; Aged; Intermediate Filament Proteins; proteiny nervové tkáně; senioři; mnohočetný myelom; Male; Female